PENGARUH FASILITAS KERJA DAN KEPUASAN KERJA TERHADAP MOTIVASI KERJA DAN DAMPAKNYA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR PEGAWAI - Mhd. Ikhwanda Nawawi; Yuliana Sari; Sarah Mardhika Lestari; Teguh Prasetyo (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
This study is to determine the effect of the effect of work facilities and job satisfaction on work motivation on employees of the Tanjung Rejo sub-district, Medan Sunggal sub-district, Medan city. The population of this research is 33 employees of Tanjung Rejo Village, Medan Sunggal Subdistrict, Medan City. The research method used is path analysis with the motivation variable as an intervening variable, and the data collection method is through a questionnaire with a Likert scale. The results showed that simultaneously working facilities and work motivation of employees of Tanjung Rejo Village, Medan Sunggal Subdistrict, Medan City. Based on the results of the analysis carried out at the 5% significance level, the conclusion that can be put forward in this study is that work facilities have a positive and significant effect on work motivation. Work motivation correctly is an intervening variable.